Self-Reported Psychosocial Health in Obese Patients before and after Weight Loss - G. Osei-Assibey; I. Kyrou; S. Kumar; P. Saravanan; K. A. Matyka (Journal of Obesity)
Psychosocial profiles were examined in 255 morbidly obese patients attending a hospital service offering access to standard weight loss therapies. 129 patients were reassessed after at least 6-month follow-up. At baseline, 51.8% and 32.7% of patients, respectively, had evidence of anxiety and depressive disorders, 24% had severe impairments in self esteem, and 29.7% had an increased risk of eating disorders. At follow-up, weight loss from baseline was significant in all 3 therapies: diet only is 0.74±1.8 kg; pharmacotherapy is 6.7±4.2 kg; and surgery is 20.1±13.6 kg. Anxiety scores improved in all three groups (𝑃<.05). Patients having pharmacotherapy or surgery had significant improvements in physical and work function and public distress compared to those having dietary treatment only (𝑃<.05). Our observational data suggest that weight management services can lead to psychosocial benefit in morbidly obese patients. Well-designed studies are necessary to examine the link between weight loss and emotional health.